Individualization of intensity thresholds on external workload demands in women`s basketball by K-Means clustering: Differences based on the competitive level - Ibáñez, S. J.; Gómez-Carmona, C. D.; Mancha-Triguero, D. (Sensors, 2022)
In previous studies found in the literature speed (SP), acceleration (ACC), deceleration (DEC), and impact (IMP) zones have been created according to arbitrary thresholds without considering the specific workload profile of the players (e.g., sex, competitive level, sport discipline). The use of statistical methods based on raw data could be considered as an alternative to be able to individualize these thresholds. The study purposes were to: (a) individualize SP, ACC, DEC, and IMP zones in two female professional basketball teams; (b) characterize the external workload profile of 5 vs. 5 during training sessions; and (c) compare the external workload according to the competitive level (first vs. second division). Two basketball teams were recorded during a 15-day preseason microcycle using inertial devices with ultra-wideband indoor tracking technology and microsensors. The zones of external workload variables (speed, acceleration, deceleration, impacts) were categorized through k-means clusters. Competitive level differences were analyzed with Mann-Whitney`s U test and with Cohen`s d effect size. Five zones were categorized in speed (<2.31, 2.31-5.33, 5.34-9.32, 9.33-13.12, 13.13-17.08 km/h), acceleration (<0.50, 0.50-1.60, 1.61-2.87, 2.88-4.25, 4.26-6.71 m/s2), deceleration (<0.37, 0.37-1.13, 1.14-2.07, 2.08-3.23, 3.24-4.77 m/s2), and impacts (<1, 1-2.99, 3-4.99, 5-6.99, 7-10 g). The women`s basketball players covered 60-51 m/min, performed 27-25 ACC-DEC/min, and experienced 134-120 IMP/min. Differences were found between the first and second division teams, with higher values in SP, ACC, DEC, and IMP in the first division team (p < 0.03; d = 0.21-0.56). In conclusion, k-means clustering can be considered as an optimal tool to categorize intensity zones in team sports. The individualization of external workload demands according to the competitive level is fundamental for designing training plans that optimize sports performance and reduce injury risk in sport.